Evolution of Water Management in the Maloutena Residential Quarter of Nea Paphos. The Hellenistic and Early Roman Periods - Romaniuk, Marcin M. (Études et Travaux, 2025)
The paper reconstructs the evolution of water management in the Maloutena residential quarter of Hellenistic and early Roman Nea Paphos (Cyprus), drawing on the analysis of water-related installations uncovered there by the Polish Archaeological Mission of the University of Warsaw (1965–2016). Structured into a four-phase periodisation spanning from the late fourth century BC to the mid-second century AD, the study traces successive transformations in local practices of water supply, usage, and disposal, considering them in their historical context with regard to their potential environmental, political, and sociocultural determinants.